(untitled) - Skarzynski, Peter (San Francisco, 2014)
The Innovator's Field Guide focuses on the most pressing innovation problems and specific challenges innovation leaders will face and offers concrete solutions, tools, and methods to overcome them. Each chapter describes a specific innovation challenge and details proven ways to address that challenge. Includes practical ideas, techniques, and leading practices. Describes common obstacles and offers practical solutions.
Keywords: Creative ability in business,New products,Đổi mới công nghệ,Khả năng sáng tạo trong kinh doanh.,Sản phẩm mới,Technological innovations; Quản lý,Management